Melatonin supplementation in the subacute phase after ischemia alleviates postischemic sleep disturbances in rats. Issue 10 (14th September 2021) - Hao, Shu‐Mei; Zhong, Zhi‐Gang; Qu, Wei‐Min; Huang, Zhi‐Li; Sun, Feng‐Yan; Qiu, Mei‐Hong
Abstract: Background: Sleep disorders are highly prevalent among stroke survivors and impede stroke recovery. It is well established that melatonin has neuroprotective effects in animal models of ischemic stroke. However, as a modulator of endogenous physiological circadian rhythms, the effects of melatonin on poststroke sleep disorders remain unclear. In the present study, we investigated how melatonin delivered intraperitoneally once daily in the subacute phase after stroke onset, influencing neuronal survival, motor recovery, and sleep–wake profiles in rats. Methods: Transient ischemic stroke in male Sprague–Dawley rats was induced with 30 min occlusion of the middle cerebral artery. Melatonin or vehicle was delivered intraperitoneally once daily in the subacute phase, from 2 to 7 days after stroke. Electroencephalogram and electromyogram recordings were obtained simultaneously. Results: Compared to the effects observed in the vehicle‐treated ischemic group, after 6 daily consecutive treatment of melatonin at 10 mg/kg starting at ischemic/reperfusion day 2, the infarct volume was significantly decreased (from 39.6 to 26.2%), and the degeneration of axons in the ipsilateral striatum and the contralateral corpus callosum were significantly alleviated. Sensorimotor performances were obviously improved as evidenced by significant increases in the latency to falling off the wire and in the use of the impaired forelimb. In addition to those predictable results of reducing brain tissue damage and mitigating behavioral deficits, repeated melatonin treatment during the subacute phase of stroke also alleviated sleep fragmentation through reducing sleep‐wake stage transitions and stage bouts, together with increasing stage durations. Furthermore, daily administration of melatonin at 9 a.m. significantly increased the nonrapid eye movement sleep delta power during both the light and dark periods and decreased the degree of reduction of the circadian index. Conclusions: Melatonin promptly reversed ischemia‐induced sleep disturbances. The neuroprotective effects of melatonin on ischemic injury may be partially associated with its role in sleep modulation. Abstract : Although sleep disturbances are highly prevalent among stroke survivors and impede post‐stroke recovery, they are still insufficiently considered in the prevention and management of stroke patients. Little attention has been paid to its physiological consequences of melatonin of regulating circadian rhythms on stroke subjects. Our results showed that in addition to the predictable effects on reducing brain damage and mitigating behavioral deficits, repeated melatonin treatment during the sub‐acute phase of stroke also ameliorated circadian rhythm disruption, alleviated sleep fragmentation, and increased sleep depth in ischemic rats. The findings revealed the ability of melatonin to quickly and promptly reverse ischemia‐induced sleep disturbances; a new perspective on how melatonin protect the brain against ischemia injury; and a suitable strategy for improving clinical outcomes in acute stroke victims.